Media Ular Tangga REHAT (REMAJA SEHAT) sebagai Inovasi Pembelajaran untuk Meningkatkan Kesehatan Reproduksi Remaja - Dewi, Utami; Harianja, Ristina Rosauli; Sihaloho, Metasari; Fenorika, Edina; Aulia, Nabila Pasya; Ramadhani, Nurhakiki; Sakinah, Radyah; Nurhaliza, Titik (Poltekes Kemenkes Tanjungpinang, 2024)
Adolescents are vulnerable to various health problems, including reproductive health, Substance Use Disorders (SUDs), sexual violence, early marriage, and low self-esteem. This problem is more complex in remote areas and islands, limited to formal education and health resources. Conventional approaches such as formal education or counselling are ineffective. Therefore, innovative, interactive, and fun learning media are needed to deliver health messages to adolescents through games. The community service aims to increase students' awareness of reproductive health issues through an innovative approach using the REHAT snakes and ladders game media. This activity did not only cover reproductive health topics such as balanced nutrition and prevention of sexual violence but also taught social values relevant to adolescents' lives. The activity was conducted at SMA Negeri 1 Mantang, Mantang Lama Village, Mantang District, Bintan Regency, on Wednesday, February 28, 2024, with 45 students as the respondents. The pre-and post-tests show that the demonstrated group has an increased understanding of the material presented. Before the activity, students' average score of understanding health issues such as balanced nutrition, reproductive health, and drug prevention was 50%. After the activity, it showed that the understanding had increased to 85%. Traditional media that does not require sophisticated technology has also proven effective in areas with limited access. Hopefully, this program can be replicated in other schools to increase the positive impact of using this educational media.